Clinical utility of ICD‐11 diagnostic guidelines for high‐burden mental disorders: results from mental health settings in 13 countries. Issue 3 (7th September 2018) - Reed, Geoffrey M.; Keeley, Jared W.; Rebello, Tahilia J.; First, Michael B.; Gureje, Oye; Ayuso‐Mateos, José Luis; Kanba, Shigenobu; Khoury, Brigitte; Kogan, Cary S.; Krasnov, Valery N.; Maj, Mario; de Jesus Mari, Jair; et al.
Abstract : In this paper we report the clinical utility of the diagnostic guidelines for ICD‐11 mental, behavioural and neurodevelopmental disorders as assessed by 339 clinicians in 1, 806 patients in 28 mental health settings in 13 countries. Clinician raters applied the guidelines for schizophrenia and other primary psychotic disorders, mood disorders (depressive and bipolar disorders), anxiety and fear‐related disorders, and disorders specifically associated with stress. Clinician ratings of the clinical utility of the proposed ICD‐11 diagnostic guidelines were very positive overall. The guidelines were perceived as easy to use, corresponding accurately to patients' presentations (i.e., goodness of fit), clear and understandable, providing an appropriate level of detail, taking about the same or less time than clinicians' usual practice, and providing useful guidance about distinguishing disorder from normality and from other disorders. Clinicians evaluated the guidelines as less useful for treatment selection and assessing prognosis than for communicating with other health professionals, though the former ratings were still positive overall. Field studies that assess perceived clinical utility of the proposed ICD‐11 diagnostic guidelines among their intended users have very important implications. Classification is the interface between health encounters and health information; if clinicians do not find that a new diagnostic system provides clinically useful information, they are unlikely to apply it consistently and faithfully. This would have a major impact on the validity of aggregated health encounter data used for health policy and decision making. Overall, the results of this study provide considerable reason to be optimistic about the perceived clinical utility of the ICD‐11 among global clinicians.